2013
DOI: 10.1089/jop.2012.0155
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antifungal Activity of Silver Nanoparticles Against Ocular Pathogenic Filamentous Fungi

Abstract: Nano-Ag, relative to natamycin, exhibits potent in vitro activity against ocular pathogenic filamentous fungi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(39 citation statements)
references
References 27 publications
0
39
0
Order By: Relevance
“…Corneal collagen cross-linking (CXL) is a relatively new technique currently been investigated in conjunction with photo-activated riboflavin (PAR) in refractory keratitis cases [102,137]. Investigations into the use of nanoparticle technology with terbinafine and silver have also shown promising results [189,214]. In addition, topical aqueous garlic extracts have been tested on rabbit keratitis models infected with A. flavus [76].…”
Section: Treatmentmentioning
confidence: 99%
“…Corneal collagen cross-linking (CXL) is a relatively new technique currently been investigated in conjunction with photo-activated riboflavin (PAR) in refractory keratitis cases [102,137]. Investigations into the use of nanoparticle technology with terbinafine and silver have also shown promising results [189,214]. In addition, topical aqueous garlic extracts have been tested on rabbit keratitis models infected with A. flavus [76].…”
Section: Treatmentmentioning
confidence: 99%
“…Results demonstrated that AgNPs had higher activity as compared to natamycin. 258 Similarly, Dar et al studied the biocidal potential of AgNPs synthesized from Cryphonectria spp. against S. typhi, E. coli, S. aureus, and C. albicans, concluding that AgNPs can be used as potential antifungal agents.…”
mentioning
confidence: 99%
“…Investigations into the use of nanoparticle technology with terbinafine and silver have shown promise [66,67]. There has been an attempt to develop an antimicrobial contact lens incorporating melimine into the lens substance [68].…”
Section: Methodsmentioning
confidence: 99%